Implant failure in bilateral metal-on-metal hip resurfacing arthroplasties: A clinical and pathological study - Uchihara, Y; Grammatopoulos, G; Munemoto, M; Matharu, G; Inagaki, Y; Pandit, H; Tanaka, Y; Athanasou, N (Springer, 2018)
Metal-on-metal hip resurfacing arthroplasties (MoMHRAs) have a high failure rate due to pseudotumour formation. It is not certain whether pseudotumours in bilateral MoMHRAs form on the basis of an adverse reaction to metal debris (ARMD) that is entirely due to a local innate and adaptive immune response to Cobalt-Chrome (Co-Cr) wear particles. To determine if there is a systemic component to ARMD in bilateral MoMHRAs, we examined the histology of ARMD in unilateral and bilateral MoMHRAs revised for pseudotumour and determined whether implant survival differed between these two groups. Periprosthetic tissue specimens from 119 hips revised for pseudotumour were examined. These were derived from 109 patients including 10 patients with bilateral MoMHRAs and 99 with sunilateral MoMHRAs including a cohort of 20 patients with bilateral MoMHRAs that had undergone only one MoMHRA revision for pseudotumour. The mean time to revision for pseudotumour of unilateral and bilateral MoMHRAs was determined. The histology of periprosthetic tissue was examined for evidence of the innate and adaptive immune response and scored semi-quantitatively. There was no significant difference in histological features of the innate / adaptive response between Group 1 bilateral pseudotumours and Group 2 and Group 3 unilateral pseudotumours. Histological features, including ALVAL scores, were similar in the periprosthetic tissues of right and left hips in Group 1 bilateral MoMHRAs. The mean time to first revision for pseudotumour of bilateral MoMHRAs (6.59 years) was not decreased compared with unilateral MoMHRAs (5.66 years) or bilateral MoMHRAs that had only one revision (7.05 years). Right and left hip pseudotumours in bilateral MoMHRAs exhibit similar histological features of the innate and adaptive immune response. Mean implant survival is not decreased in bilateral compared with unilateral MoMHRA cases. The findings suggest that pseudotumour formation is due more to a local than a systemic innate /adaptive immune response to components of metal wear.